Approximations in Sobolev spaces by prolate spheroidal wave functions - Bonami, Aline; Karoui, Abderrazek (Applied and computational harmonic analysis, 2017)
Recently, there is a growing interest in the spectral approximation by the Prolate Spheroidal Wave Functions (PSWFs) ψn,c,c>0. This is due to the promising new contributions of these functions in various classical as well as emerging applications from Signal Processing, Geophysics, Numerical Analysis, etc. The PSWFs form a basis with remarkable properties not only for the space of band-limited functions with bandwidth c, but also for the Sobolev space Hs([−1,1]). The quality of the spectral approximation and the choice of the parameter c when approximating a function in Hs([−1,1]) by its truncated PSWFs series expansion, are the main issues. By considering a function f∈Hs([−1,1]) as the restriction to [−1,1] of an almost time-limited and band-limited function, we try to give satisfactory answers to these two issues. Also, we illustrate the different results of this work by some numerical examples.